The prospect of sea cucumber (Holothuroidea sp) agribusiness development in south Sulawesi Province. Issue 1 (March 2020) - Asriani; Made, S; Tahang, H
Abstract: Sea Cucumber ( Holothuroidea sp) is one of the fisheries commodities that has good prospects to be developed because of its high economic value and potentially promising market demand both in the local and international markets. Data from the Ministry of Maritime Affairs and Fisheries throughout 2012-2016 shows the trend of sea cucumber exports has increased from 900-2000 tons/year. As for China, Singapore and Taiwan remain the main customers. Demand for sea cucumbers, especially for exports, has increased every year so that fishing and hunting in the sea take place more intensively causing a decrease in catches from the sea. Sea cucumbers can be processed into food and traded in various forms in the form of: food supplement products, cosmetic products, and medicinal products which are efficacious for the treatment of various diseases. In the Province, many are engaged in sea cucumbers by implementing the agribusiness system which is not yet optimal. The influence of internal and external factors and the need for sea cucumber development strategies. This study aims to determine the level of financial feasibility, the influence of internal and external factors, sea cucumber agribusiness development strategies. The study was conducted in South Sulawesi Province with locations in Barrang Lompo, Takalar, and Selayar, using survey methods with data collection techniques through direct observation, interviews and observations. Data were then analyzed using financial feasibility analysis, SWOT analysis, and QSPM analysis. The results showed that sea cucumber business is feasible to run, internal factors (strengths: high sea cucumber prices, weaknesses: use of fishing gear not in accordance with work safety standards) and external factors (high market potential opportunities, threats limited stock), Sea Cucumber has good prospects going forward with the Cultivation strategy, the application of processing technology, Optimizing business and market potential, Increasing capital cooperation.